234k views
1 vote
How to solve f(x)=2x+1 when x=a-b?​

2 Answers

2 votes

Do a u-substitution!

Let u = 2x-1.

Then x = (u+1)/2.

Substituting into f(2x-1) = x, we get f(u) = (u+1)/2.

Thus, f(2) = (2+1)/2 = 3/2.

User DanielZanchi
by
5.3k points
2 votes

Answer:f(2) = 3/2

Explanation:

Let u = 2x-1.

Then x = (u+1)/2.

Substituting into f(2x-1) = x, we get f(u) = (u+1)/2.

Thus, f(2) = (2+1)/2 = 3/2.

User Codingrose
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.